PERAN KONSELING INDIVIDU DENGAN TEKNIK EXPERIENTIAL LEARNING UNTUK MENINGKATKAN SELF CONFIDENCE PADA PESERTA DIDIK KELAS X 7 SMA NEGERI 1 COLOMADU TAHUN PELAJARAN 2025/2026 - Liawati, Emi; Heru Sri Suryanti, Hera; Adi Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the role of individual counseling services using experiential learning techniques in improving self-confidence among the tenth grade students of SMA Negeri 1 Colomadu for the 2025/2026 academic year. This research was conducted at SMA Negeri 1 Colomadu. The subject of this study was one student from Grade X 7. The research method used was descriptive qualitative research. The data analysis technique employed was based on the Miles & Huberman model, which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The data collection techniques used were interviews, observation, and documentation. According to the results of the study, the experiential learning technique helped students gain direct experience that can be utilized as a learning process in building self-confidence. Based on the research findings, it can be concluded that individual counseling services using experiential learning techniques can assist in improving the self-confidence of Grade X 7 students at SMA Negeri 1 Colomadu for the 2025/2026 academic year.